Respuesta del cultivo de pimiento (Capsicum annuum l.) A la utilización de bioestimulantes en época lluviosa en la zona de Buena Fe. - Zamora Muñoz, José Manuel (2015)
Considering the low performance and increasingly large amount of fertilizer applied to crops, it has taken the initiative to conduct trials to find alternative fertilizer to increase production and productivity of crops, in this case the pepper. Therefore it was conducted this investigation taking aim to increase crop yield of pepper, for which the following specific objectives were defined: to evaluate the effect of biostimulants on growth of pepper crop, identify the bioestimulante increasing the pepper crop production and make economic analysis of the treatments under study. The trial was established on grounds Hcda "Selma Sayra" located at Km 27 of the road Buena Fe - Santo Domingo, using genetic material as the hybrid Magali. Design randomized complete block was used with factorial arrangement 3x4 + 1 in 3 repetitions, studying four bioestimulantes: Bioactive Plus, Crop Plus, Kinetin and Master in three doses, whose interactions were compared to a control (Evergreen). Duncan test was used 95% chance to establish statistical difference between factors and treatments under study, with asperciones of bioactive-plus could be observed as long as diameter and fruit weight in high dose of 0.650 lt / He has also had the highest performance 20546.9 kg / ha and therefore a cost benefit of $ 3.10.